(3eSCdI aj dG Gdg GdG Gddgs - (3eMehO Hf YeQ Hf eMeO Hf CMeO GdNhGQRej GdReNTQqj, LGQ Gddg, CHh GdbGSe,(B538 (3g`s
(3ChdgG (B:s
(3GYde Gf eJbOei GdTjhN hLOhG Edi bhdfG dG Edg EdG Gddg cdGe ZjQ JGe hdG eSJbd HfaSg s
(3BNQgG (B:s
(3Gfg SeY jhe GdGMO dGSja GdG Ph GdZaGQ hdG ai GdEYdi aJHjf hJMbb Gf GdeYfi eG PcQfGg JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdNGeS hGdYTQhfjfs
(3GfXQg eY GdeNWhW Qbe (B292 (3ef faS GdHYKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B178 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B186 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B402s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds